Comportamiento agronomico y productivo de cuatro variedades de mani (ArachishypogaeaL.). - Carranza Vargas, Jaime Alfredo (2012)
The research entitled "AGRICULTURE AND PRODUCTIVE BEHAVIOR OF FOUR VARIETIES OF PEANUT (Arachishypogaea L.)" was held at the Farm "Envy", owned by Mrs. Martha Vargas located at Km 27 of the enclosure via Santo Domingo Quevedo " The Tranca "belonging to the Canton Good Faith, whose location is 1 ° 3 '18'' south latitude and 79 ° 25' 24'' W, at a height of 78 m and lasted 120 days . .....